Recommendations to improve adverse event reporting in clinical trial publications: a joint pharmaceutical industry/journal editor perspective. (3rd October 2016) - Lineberry, Neil; Berlin, Jesse A; Mansi, Bernadette; Glasser, Susan; Berkwits, Michael; Klem, Christian; Bhattacharya, Ananya; Citrome, Leslie; Enck, Robert; Fletcher, John; Haller, Daniel; Chen, Tai-Tsang; et al.
Abstract : Medical Publishing Insights & Practices (MPIP)—a partnership among pharmaceutical companies and the International Society for Medical Publication Professionals—aims to identify ways to improve transparency and credibility in publishing the results of industry sponsored research. This article provides guidance from MPIP on clinically relevant and more informative adverse event reporting, previously identified by journal editors as a significant unmet need to improve patient care and increase the credibility of industry sponsored publications. Our recommendations include highlighting adverse events of most relevance to practitioners and their patients, avoiding broad summary statements such as "generally safe" or "well tolerated, " and including more detailed adverse event data (where appropriate) to offer additional clinically important insight. These recommendations complement the earlier recommendations in the Consolidated Standards of Reporting Trials (CONSORT) Harms Extension. Although developed for industry sponsored trials, the adoption of our recommendations would enhance adverse event reporting in clinical research publications regardless of the funding source and thereby facilitate clinical decision making.